Foreign trade and economic development in Africa : a historical perspective - Neumark, Solomon Daniel (Stanford, Calif. : Food Research Institute, Stanford University, 1964)
This book is about some of the dynamic factors of the social -historical process in Africa.
Includes bibliographical references and index.
oo 01/11/2018
Loans
Keywords: Economic development; Africa